Low-dose metformin targets the lysosomal AMPK pathway through PEN2 - Ma, Teng; Tian, Xiao; Zhang, Baoding; Li, Mengqi; Wang, Yu; Yang, Chunyan; Wu, Jianfeng; Wei, Xiaoyan; Qu, Qi; Yu, Yaxin; Long, Shating; Feng, Jin-Wei; et al. (Nature (London), 2022)
Metformin, the most prescribed antidiabetic medicine, has shown other benefits such as anti-ageing and anticancer effects 1 – 4 . For clinical doses of metformin, AMP-activated protein kinase (AMPK) has a major role in its mechanism of action 4 , 5 ; however, the direct molecular target of metformin remains unknown. Here we show that clinically relevant concentrations of metformin inhibit the lysosomal proton pump v-ATPase, which is a central node for AMPK activation following glucose starvation 6 . We synthesize a photoactive metformin probe and identify PEN2, a subunit of γ-secretase 7 , as a binding partner of metformin with a dissociation constant at micromolar levels. Metformin-bound PEN2 forms a complex with ATP6AP1, a subunit of the v-ATPase 8 , which leads to the inhibition of v-ATPase and the activation of AMPK without effects on cellular AMP levels. Knockout of PEN2 or re-introduction of a PEN2 mutant that does not bind ATP6AP1 blunts AMPK activation. In vivo, liver-specific knockout of Pen2 abolishes metformin-mediated reduction of hepatic fat content, whereas intestine-specific knockout of Pen2 impairs its glucose-lowering effects. Furthermore, knockdown of pen-2 in Caenorhabditis elegans abrogates metformin-induced extension of lifespan. Together, these findings reveal that metformin binds PEN2 and initiates a signalling route that intersects, through ATP6AP1, the lysosomal glucose-sensing pathway for AMPK activation. This ensures that metformin exerts its therapeutic benefits in patients without substantial adverse effects. The molecular target of the antidiabetic medicine metformin is identified as PEN2, a subunit of γ-secretases, and the PEN2–ATP6AP1 axis offers potential targets for screening for metformin substitutes.